Ergogenic aids as a means for increasing athlete working capacity in the high altitude environment - Oliynyk, S.; Shevchenko, V. (International Journal of Applied Sports Sciences, 2009)
Dietary supplement AntihotR was tested as a potential means for increasing human working capacity in a high altitude environment. During three days the volunteers (athletes specializing in mountaineering) climbed to the height of 3,700 m above sea level by marches of 15 km each with a load of 35-40 kg. Twenty nine young men aged 20-35 years old participated in the trip, and 15 of them were taking AntihotR in capsules, 1 capsule (0.5 g) three times a day during a meal, for 4 days. The other 13 men, who were included in the control group, were taking a placebo under a similar routine. Besides hypoxic hypoxia the ascent was complicated by the night temperature fall to -5°C, preventing the climbers from having rest and recreation. It was registered that with taking AntihotR the climbing was easier to tolerate. The number of complaints recorded in a mountain experience questionnaire decreased, and, above all, the course of halt recreation had run much quicker. In the upland environment, the improvement of a feeling of health was recorded, physical loads got easier to overcome, and fatigue was lowered. A distinct decrease of hypoxic hypoxia was registered. Symptomatology relevant to the presentations of acute mountain pathology developed to a minor ratio and virtually did not affect on the volunteers' functional condition and their working capacity. In comparison to the control group the average number of complaints decreased to 4 times less, including cerebral and common complaints which decreased by 6 times less, cardiorespiratory ones . to 2.5 times less, and digestive and excretory complaints . 20 times less. These results are sure to argue for distinct antihypoxic action by AntihotR. Heart rate is a general parameter of physiological function tension. At the post-ascent examination of the climbers who had taken AntihotR, it remained lower than background meaning both at rest and while conducting a loading test by 5.5 and 11.4%, respectively. In aggregate with a reliable increase of breath-holding (Stange test) by 25.5% against taking AntihotR, results argue for a favorable preparation impact on the functions of the oxygen transportation system, rapid and complete removal of oxygen debt and, maybe, as a whole, for a decrease of tension level in the body´s physiological systems, thus, facilitating adaptation and working capacity in a high altitude environment. Therefore, AntihotR has displayed high efficacy in increasing tolerance to unfavorable factors of environment in high altitude as well as in facilitating tolerance to physical loading and maintaining a feeling of well-being during the whole stay in the mountains.